TEORI H SEBAGAI ILMU WAHYU DAN TURATS DALAM ISLAM - Roikhan, Roikhan (Jurnal Ushuluddin, 2016)
The concept of conventional found the form of M theory that almost able to unite the dimensions of time and space, but it still leaves unclear structure and systematics of the concept itself. Islam in the Qurâan Surah al-Hijr [15]: 87 was able to interpret the dimensions of time and space by tiered meaning of significance 7 and Qurâan. Hâ Theory as a formula could be more better and more precisely, because it can synchronize with the symbols of root word of Islam. The Hahslm equation H=Ah (SLM) can be obtained by a single theory that is also based on values of Islam and derived from al-Qurâan the word of Allah. This God equation would be the answer for the conventional scientific development that based on empirical values together with science of Islam that based on the value of worship or intangible value. In the end, the human civilization is able to break through the impasse of united science that stagnates in order of different dimensions. And Islam will be recognized as a single formula in human thought